Disaffiliation from the Evangelical Lutheran Churches in the Nordic Countries: Mistrust in the Churches, Changing Worldviews, or Something else? - Lemos, Carlos Miguel (Secularism and Nonreligion, 2024)
In this article, I used data from the 2018 Religion survey of the International Social Survey Programme to compare Protestants affiliated with the Evangelical Lutheran Churches and the religiously unaffiliated in the five Nordic countries. I was primarily interested in significant predictors of disaffiliation. I found that the differences between Protestants and the religiously unaffiliated within countries are far more pronounced than the differences between these two groups across the countries, and that the lack of confidence in churches is a very strong predictor of disaffiliation. The religious or nonreligious socialization during the formative period (described by the parents’ affiliation and the frequency of churchgoing during the formative period) is also an important predictor of disaffiliation. Ceasing to believe in God and having negative perceptions about the relevance and timeliness of religion are also significant predictors of disaffiliation, albeit weaker than mistrust in the Churches and religious or nonreligious upbringing. In addition, there are important differences between the countries: the odds of disaffiliating in Norway, Sweden, and (especially) Finland are significantly higher than in Denmark. These differences are due to path-dependent and country-specific factors unaccounted-for by the other predictors. Moreover, disaffiliation occurs across a wide range of ages, and only the elderly (75 years or more) seem to be an exception.